Evaluasi Kinerja Program Rehabilitasi Mental terhadap Orang Dengan Gangguan Jiwa - Andi Subandi; Dwi Noerjoendianto; La Ode Reskiaddin (Mahesa Research Center, 2022)
Currently, it is estimated that there are 450 million peoples uffering from mental disorders (WHO,2016). The recurrence rate at the Jambi Provincial Mental Hospital, which is the only mental hospital in Jambi Province is 89.2%. The purpose of this research his to find out how mental rehabilitation is given at this hospital. This study use the evaluation framework of the CDC. Step 1, the stakeholders consulted were the head of the field, the head of the section, the head of the room. Step-2 there is no special model/design in report generation. Reports are based on daily visits and become monthly reports. Step-3, the report in this installation doesn’t use any special evaluation model in the development program and currently in the process of facilities and infrastructure that are still lackingare psychologists in installation and religious therapists for non-Muslims. For step-4 data collectionare from daily record, whether the patient can or cannot or less in participating in the therapy activities, there is no special team in program evaluation. Step-5, to understand the findings, the stakeholders didn’t find any problems, drawn based on the monthly results. Step-6 every stakeholders can see the report result. Mental rehabilitation activities have been going well, in the evaluation of the program evaluation, need a model that can support the program description so that it can help the program development stage. The hospital also needs to cooperate with institutions/organizations tohelp patients that just discharged from the hospital toreceive direction and prevent recurrence patients